2016
DOI: 10.3892/ijo.2016.3331
|View full text |Cite
|
Sign up to set email alerts
|

miR-200/ZEB axis regulates sensitivity to nintedanib in non-small cell lung cancer cells

Abstract: Nintedanib (BIBF1120) is a multi-targeted angiokinase inhibitor and has been evaluated in idiopathic pulmonary fibrosis and advanced non-small cell lung cancer (NSCLC) patients in clinical studies. In the present study, we evaluated the antitumor effects of nintedanib in 16 NSCLC cell lines and tried to identify microRNA (miRNA) associated with sensitivity to nintedanib. No correlations between FGFR, PDGFR and VEGFR family activation and sensitivity to nintedanib were found. The difference in miRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…These discrepancies may be partially explained by the various sources of the cases studied, different detection techniques and different platforms used. It is reported that members of the miR-200 family can reverse epithelial-mesenchymal transition (EMT) by increasing E-cadherin expression and decreasing ZEB1, ZEB2 and β-catenin expression, further inhibiting cancer cell invasion and migration (31,(37)(38)(39)(40). Notably, EMT mechanisms are distinct in various malignancies, and the expression of EMT markers (E-cadherin and ZEB) is inconsistent in diverse types of cancers and different histological types of the same cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be partially explained by the various sources of the cases studied, different detection techniques and different platforms used. It is reported that members of the miR-200 family can reverse epithelial-mesenchymal transition (EMT) by increasing E-cadherin expression and decreasing ZEB1, ZEB2 and β-catenin expression, further inhibiting cancer cell invasion and migration (31,(37)(38)(39)(40). Notably, EMT mechanisms are distinct in various malignancies, and the expression of EMT markers (E-cadherin and ZEB) is inconsistent in diverse types of cancers and different histological types of the same cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been demonstrated to be differently expressed between normal and cancer cells, and aberrant expression of miRNAs has a key association with the development, invasion, metastasis, and prognosis of NSCLC. In addition, miRNAs modulate cancer therapy response and resistance ; however, limited evidence has been obtained for miRNA‐mediated signaling networks that regulate progression and chemoresistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor effects of nintedanib on EGFR mutant lung cancer are expected to be mediated by the angiogenesis pathway and nintedanib target pathways, such as fibroblast growth factor receptor, Src. A recent preclinical study demonstrated that nintedanib restores EGFR-TKI sensitivity by reversing TGF-B1-induced EMT via miR-200b and miR-141 upregulation and ZEB1 downregulation [15].…”
Section: Discussionmentioning
confidence: 99%